Yukaku (red-light district) and city planning in Japanese colonial cities in Taiwan, 1895-1945 - Sammonji, Masaya (International Planning History Society Proceedings, 2018)
In 1895, Taiwan (Formosa) was ceded to Japan by the Qing dynasty. In the earliest period of the Japanese rule, a crowd of Japanese prostitutes immigrated to Taiwan, which opened an era when sex industry of both Japanese and locals appeared broadly in the cities. Then, aiming to solve sanitary and security issues, Japanese colonial government started to set “kashizashiki designated area (also called yukaku area simply)” in each city in 1896, and allowed prostitutes to do their business only inside the area. It also provided the rough location planning of colonial cities far earlier than other well-studied urban policies or plannings, such as the “city improvement plannings (shiku-kaisei)” started in 1900 and so on. Thus, in this context, these designations can be considered as the earliest “silent” planning of the Japanese colonial cities. After that, some yukakus moved to another location in the cities once or more, in response to city growth and progress of the “city improvement planning”. This study found that there were yukakus in 16 cities of colonial Taiwan in total, and the meanings and grounds of each location changed in response to the progress of urban planning or urban developing.